Development of electronic training and telescoring tools to increase the surge capacity of dicentric chromosome scorers for radiological/nuclear mass casualty incidents. (February 2019) - Balajee, Adayabalam S.; Escalona, Maria; Iddins, Carol J.; Shuryak, Igor; Livingston, Gordon K.; Hanlon, Don; Dainiak, Nicholas
Abstract: Dicentric chromosome assay (DCA) is most frequently used for estimating the absorbed radiation dose in the peripheral blood lymphocytes of humans after occupational or incidental radiation exposure. DCA is considered to be the "gold standard" for estimating the absorbed radiation dose because the dicentric chromosome formation is fairly specific to ionizing radiation exposure and its baseline frequency is extremely low in non-exposed humans. However, performance of DCA for biodosimetry is labor intensive and time-consuming making its application impractical for radiological/nuclear mass casualty incidents. Realizing the critical need for rapid dose estimation particularly after radiological/nuclear disaster events, several laboratories have initiated efforts to automate some of the procedural steps involved in DCA. Although metaphase image capture and dicentric chromosome analysis have been automated using commercially available platforms, lack or an insufficient number of these platforms may pose a serious bottleneck when hundreds and thousands of samples need to be analyzed for rapid dose estimation. To circumvent this problem, a web-based approach for telescoring was initiated by our laboratory, which enabled the cytogeneticists around the globe to analyze and score digital images. To further increase the surge capacity of dicentric scorers, we recently initiated a dicentric training and scoring exercise involving a total of 50 volunteers at all academic levels without any prerequisite for experience in radiation cytogenetics. Out of the 50 volunteers enrolled thus far, only one outlier was found who overestimated the absorbed radiation dose. Our approach of training the civilians in dicentric chromosome analysis holds great promise for increasing the surge capacity of dicentric chromosome scorers for a rapid biodosimetry in the case of mass casualty scenarios. Highlights: Dicentric Chromosome Assay is the "gold standard" for estimating an individual's absorbed radiation dose after exposure. Electronic training and scoring tools were developed for increasing the surge capacity of dicentric chromosome scorers. With the exception of one outlier, all the volunteers estimated the absorbed radiation dose fairly accurately. Our approach for increasing the surge capacity of dicentric chromosome scorers holds great promise for rapid biodosimetry.